The grand design [compact disc, unabridged] - Hawking, Stephen, 1942-2018 (Random House Audio, 2010)
Mixes cutting-edge physics to answer three key questions-- Why is there something rather than nothing? Why do we exist? Why this particular set of laws and not some other? Explains that scientists are approaching what is called "M-theory," a collection of overlapping theories (including string theory) that fill in many (but not all) the blank spots in quantum physics. This collection is known as the "Grand Unified Field Theories."